2001
DOI: 10.1021/jm001079l
|View full text |Cite
|
Sign up to set email alerts
|

2- and 3-Substituted 1,4-Naphthoquinone Derivatives as Subversive Substrates of Trypanothione Reductase and Lipoamide Dehydrogenase from Trypanosoma cruzi:  Synthesis and Correlation between Redox Cycling Activities and in Vitro Cytotoxicity

Abstract: Trypanothione reductase (TR) is both a valid and an attractive target for the design of new trypanocidal drugs. Starting from menadione, plumbagin, and juglone, three distinct series of 1,4-naphthoquinones (NQ) were synthesized as potential inhibitors of TR from Trypanosoma cruzi (TcTR). The three parent molecules were functionalized at carbons 2 and/or 3 by various polyamine chains. Optimization of TcTR inhibition and TcTR specificity versus human disulfide reductases was achieved with the 3,3'-[polyaminobis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
200
0
19

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(225 citation statements)
references
References 62 publications
6
200
0
19
Order By: Relevance
“…[5] and [26] The native functions of these enzymes involve the NAD(P)Hdependent reduction of disulfide bonds in proteins or oxidised versions of low molecular weight thiols such as glutathione. The enzyme-mediated toxicity of quinones/naphthoquinones is a consequence of their enzymatic reduction to semiquinone radicals (Fig.…”
Section: Subversive Substrate Properties With Mtrmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] and [26] The native functions of these enzymes involve the NAD(P)Hdependent reduction of disulfide bonds in proteins or oxidised versions of low molecular weight thiols such as glutathione. The enzyme-mediated toxicity of quinones/naphthoquinones is a consequence of their enzymatic reduction to semiquinone radicals (Fig.…”
Section: Subversive Substrate Properties With Mtrmentioning
confidence: 99%
“…Naphthoquinones are widely distributed in plants, fungi and some animals 1 and many are found to exhibit an interesting range of pharmacological properties including antibacterial, [2] and [3] antiviral, 4 trypanocidal, 5 anticancer, 6 antimalarial, [7] and [8] and antifungal 9 activity. Other quinone-related scaffolds such as 2-H-pyran-3(6H)-one derivatives 10 natalensis 12 and that of diospyrin 22, isolated from this plant, was observed against drugresistant strains of M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that quinones, especially 1,4-naphthoquinones such as plumbagin 78, can induce oxidative stress in trypanosomes (T. congolense 61 and T. cruzi 62 ). This may be explained by their reduction to semi-quinone radicals by enzymes such as those present in the mitochondrial electron transport chain and the trypanothione reductase, a key enzyme of the trypanosomal antioxidant thiol metabolism.…”
Section: Quinonesmentioning
confidence: 99%
“…glutathione reductase, lipoamide dehydrogenase, and trypanothione reductase, has been studied in significant detail (26 -28). The interactions with quinones may also concomitantly inhibit the normal reactions of these enzymes (29). Previously, studies of mammalian TrxR regarding interactions with quinones include the demonstrated reduction of ubiquinone-10, 2-methyl-1,4-naphthoquinone, and alloxan (14,30).…”
mentioning
confidence: 99%